A Survey on Continuing Education of Teachers in Educational Robotics - Oliveira, Denilton Silveira; Garcia, Luciane Terra Dos Santos; Gonçalves, Luiz Marcos Garcia (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2021: Anais do XIII Simpósio Brasileiro de Robótica e XVIII Simpósio Latino Americano de Robótica, 2021)
This survey paper analyzes existing works on continuum formation in Educational Robotics. We follow a systematic review approach coming up with a set of strictly related papers that are analyzed in more detail later. About a half of the analyzed works have shown some aspects of continuity. We observe a growing in the pedagogical use of robotics in education in several countries. Also, we observe that the projects that have more continuity as a training proposal are those that present support from institutions promoting local, or even national, public policies. These projects have had a longer-term existence, thus implementing more consolidated pedagogical practices for Educational Robotics.